Oncopunt, a Video-Portal to Improve Oncological Skills of Home Care Nurses: Usability, User-Experience and Added Value for Clinical Practice - Ryanne JM Lemmens; Joachim Gregoor; Annemie IF Spooren (Journal of Human Health Research, 2017)
Homecare is very important in oncology care since cancer patients are discharged more and more earlier from the hospital and receiving ambulatory treatments. Homecare nurses have a more general broad educational background, with less specialization regarding specific care, like oncology care. The aim of this study is to develop and test a cross-platform application (named Oncopunt) for homecare nurses involved in oncology care to provide specific nurse-centred information via digital media about skill guidelines specific for oncology care. This study was set-up as a non-experimental feasibility and satisfaction study with one measurement moment to collect information about usability, user-experience and added value of Oncopunt using the System Usability Scale (SUS) and an additional questionnaire. The cross-platform application Oncopunt was build using Drupal and Vimeo and consists of a homescreen, filter/search function and watch-function (full video panel, chapter panel and FAQ). Seventeen homecare nurses completed all questionnaires. The mean SUS score was 83,8 (stdev 11,6) and Oncopunt was rated positively regarding video content, technical issues, website layout, quality of care and user satisfaction. Oncopunt is developed to provide homecare nurses specific nurse-centred information about skills specific for oncology care via digital media . It was rated good on usability, user-experiences and added value for clinical practice.
Keywords: Oncology Nursing